Epinephrine Deteriorates Pulmonary Gas Exchange in a Rat Model of Bupivacaine-Induced Cardiotoxicity: A Threshold Dose of Epinephrine. Issue 3 (May 2017) - Wang, Quan-Guang; Wu, Cong; Xia, Yun; Dong, Jiao-Jiao; Lin, Ting-Ting; Liu, Qiao-Yan; Papadimos, Thomas J.; Xu, Xu-Zhong
Abstract : Background and Objective: The study goal was to compare the effect of epinephrine in different doses on pulmonary gas exchange in a rat model of bupivacaine-induced cardiac depression. Methods: Twenty-four adult male Sprague-Dawley rats were divided into 4 groups (n = 6), and each group received a bupivacaine infusion (2.5 mg/kg per minute, 6 minutes) via the left femoral vein to induce cardiac depression. At the end of the bupivacaine infusion, each group was immediately given either isotonic sodium chloride solution (normal saline; NS group), 5-μg/kg epinephrine (Epi5 group), 10-μg/kg epinephrine (Epi10 group), or 20 μg/kg epinephrine (Epi20 group). Left atrial pressures were monitored for 20 minutes after epinephrine was administered (as was the NS group). Arterial blood gas analyses were performed before bupivacaine infusion and at the end of the 20-minute monitoring period. Results: The Epi10 and Epi20 groups had lower pH ( P = 0.02 and P < 0.001, respectively) and PaO2 ( P = 0.049 and P < 0.001, respectively), and a higher PaCO2 ( P < 0.001 and P < 0.001, respectively) compared with the NS group. There were no statistical differences between the Epi5 and NS groups in pH, PaCO2, or PaO2 . Left atrial systolic pressure was higher in the Epi10 group ( P = 0.002) and the Epi20 group ( P < 0.001) within 2 minutes of epinephrine administration. There was no statistical difference between the Epi5 and NS groups in left atrial systolic pressure. Conclusion: A single injection of 10 μg/kg epinephrine or greater was associated with deterioration of pulmonary gas exchange in our rat model of bupivacaine induced cardiac depression.